Implementation of Public Facilities Quick Response Program in Sukabumi City - Eni Rohaeni (Jurnal Mantik, 2021)
Sukabumi city is an inter-city inter-provincial crossing area, the intensity of the use of this provincial road causes 75% damage so that the accident rate increases by 90%, the Sukabumi government makes an acceleration program by making a team that responds quickly to public facilities, this study aims to see how the implementation of the public facilities fast date program in the city of Sukabumi. This study uses a qualitative approach with a descriptive method. The results of the study explain that the purpose of the formation of the URC Team for Patching Jalan. The first objective is to maintain road performance in good condition. The second objective is to reduce accidents caused by road damage. The third objective is to support economic growth in Sukabumi City.